Growth hormone deficiency interferes with dynamic brain networks in short children. (August 2022) - Tang, Jing; Xia, Yikai; Liu, Naici; Li, Lan; Zou, Pinfa; Zhu, Pingyi; Shan, Xiaoou; Lui, Su; Lu, Yi; Yan, Zhihan
Abstract: Purpose: This study aimed to explore the disparities in dynamic brain networks between children with growth hormone deficiency (GHD) and idiopathic short stature (ISS, non-growth hormone deficiency). Methods: This study enrolled 65 children with GHD and 60 sex- and age-matched children with ISS. Resting-state functional magnetic resonance imaging (rs-fMRI) was performed for all participants to obtain information on dynamic regional homogeneity (dReHo) and functional connectivity (FC) in dynamic (dFC) or static (sFC) state. The rs-fMRI metrics were subsequently compared between the GHD and ISS groups. Results: Compared to the ISS group, the GHD group showed significant dynamic abnormalities in intra-networks of the central executive and cerebellar networks and in inter-networks of the central executive network to attentional, sensorimotor, and visual networks, as well as cerebellar network to default mode, sensorimotor, and visual networks. In addition, FC changes in the dynamic state were different from those in the static state. Conclusions: The abnormal dynamics in intra- and inter-networks involved in cognitive, emotional, and motor functions in children with GHD extend the knowledge on brain functional alterations in children with GHD as reflected by dynamic changes in macroscopic neural activity patterns. These findings may help explain how GHD leads to various behavioral and cognitive deficits in children with short stature. Highlights: The study is the first to explore the changes in dynamic brain networks in short children with GHD. GHD induces dynamical abnormalities in intra- and inter-networks of brain involved in cognitive, emotion, and motor functions. The combination of sFC and dFC may provide more comprehensive perspectives on the imbalanced communication within the brain and the neuropathological changes associated with GHD.